(Un)contested evidence: scientific literature, systematic reviews and the politics of evidence in the introduction of HPV vaccines in Colombia (2019)
This paper analyses the tensions between scientific literature and systematic reviews in the production of evidence in healthcare. Systematic reviews are devices developed – within evidence-based medicine – to navigate the complexities of scientific literature promising a clear and simple account of the knowledge on a particular issue. However, in practice, systematic reviews have a more complex relation with literature. Systematic reviews are shaped according to the interest of the local groups that produce them. In this paper, I explore the formatting, making and managing of systematic reviews of evidence relating to HPV vaccines in Colombia. This case shows the ways in which systematic reviews mediate between the requirement of presenting the evidence that emerges from the international literature and the necessity of having data locally relevant. © 2018 Foundation for the Sociology of Health and Illness.